Effect of rearfoot valgus on biomechanics during barbell squatting: A study based on OpenSim musculoskeletal modeling - Lu, Zhenghui; Li, Xin; Rong, Ming; Baker, Julien S.; Gu, Yaodong (Frontiers in Neurorobotics, 2022)
Background Barbell squats are commonly used in daily training and rehabilitation. Injuries are not common when the posture is standard, but the wrong posture can lead to injuries. Rearfoot valgus is a common foot abnormality that may increase the risk of injury during sports. The purpose of this study was to compare the biomechanics of lower limbs in normal foot and valgus patients during barbell squat. Methods In this study, 10 participants with normal foot shape and 10 participants with rearfoot valgus were enrolled. The joint angle, joint moment, and range of motion of hip, knee, and ankle joints were collected under 0, 30, and 70% one-repetition maximum (RM) load, where discrete data are statistically analyzed using the independent sample t-test, and continuous data are statistically analyzed using one-dimensional parameter statistical mapping. Results In barbell squats, the range of motion and the joint moment of the hip, knee, and ankle in the rearfoot valgus participants were significantly larger than those in normal foot participants (p < 0.05). The participants with rearfoot valgus had a more significant knee valgus angle when squatting to the deepest (p < 0.05). In addition, with the increase in load, the participants with rearfoot valgus showed greater standardized medial knee contact force (p < 0.05). In the process of barbell squats, the participants with rearfoot valgus showed no significant difference in the foot valgus angle when compared with the normal foot shape (p > 0.05). Conclusions The valgus population showed a greater range of joint motion when performing barbell squats and showed genu valgus and greater medial knee contact force, which may increase the risk of musculoskeletal and soft tissue damage such as meniscus wear. In addition, there was no significant difference in the rearfoot valgus angle between people with rearfoot valgus and people with normal foot shape during squatting, so barbell squatting may correct valgus to a certain extent.